High-voltage material with single-crystal particle morphology, preparation method of high-voltage material and battery
Through the combination of high-speed ball milling and coating materials, high-voltage materials with single-crystal particle morphology are prepared, which solves the problem of high-nickel content materials collapsing under high pressure, improves the energy density and safety performance of the materials, and achieves environmental protection Production.
Patent Information
- Application Number
- CN202310895162.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
The existing high-nickel ternary materials have collapse problems under high-voltage charging and discharge, and the use of a large number of acid and alkali solutions during the production process leads to environmental protection problems. The compaction density of the material is not high, the residual alkali content is high, and the safety performance is low.
The high-speed ball milling method is used to mix solid nickel salts, cobalt salts, manganese salts, lithium compounds and oxides or acid salts of doping substances. After calcination, the main crystal phase is obtained, and then mixed with the coating material at high speed. After calcination, the main crystal phase is obtained. High voltage materials with single crystal grain morphology.
It improves the stability and energy density of the material under high pressure, reduces the amount of residual alkali, improves the safety and circulation performance of the material, and avoids the problem of waste water and waste discharge.
Smart Images

Figure CN119340352A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a high-voltage material with single-crystal particle morphology, a preparation method thereof, and a battery. Background Art
[0002] The advantages of ternary materials such as high specific capacity, environmental friendliness, and no memory effect are driving their widespread use in people's daily lives, becoming a source of portable power, and their energy density is also constantly increasing. At present, the development direction of ternary materials is mainly high voltage or high nickel content. Among them, the specific capacity of high nickel content materials is relatively high. When the molar ratio of nickel content is greater than 0.8, its 0.1C discharge specific capacity can reach more than 200mAh / g in the voltage range of 3.0V to 4.3V. However, high nickel content materials still have the following disadvantages: (1) The compaction density is not high, which limits the further improvement of energy density; (2) The total residual alkali content is high, resulting in poor high temperature storage performance of the battery cell; (3) High nickel content materials have low safety performance and are prone to fire.
[0003] In addition, the current production of this type of material mainly uses the co-precipitation method to obtain the precursor, which is obtained by mixing the precursor with a lithium salt and then calcining it. The main disadvantage of this method is that the precursor requires a large amount of acid and alkali solution to react, which poses an environmental problem, and the obtained material is a quasi-single crystal material. Summary of the invention
[0004] The purpose of the present invention is to provide a high voltage material with a single crystal particle morphology. The high voltage material is a single crystal morphology, has a high compaction density and energy density, and has a low residual alkali content, and is suitable for charging and discharging at a high voltage of 4.4V.
[0005] Another object of the present invention is to provide a method for preparing a high voltage material having a single crystal particle morphology, which method is simple, easy to operate, and suitable for stable production.
[0006] The third object of the present invention is to provide a method for preparing a battery, which is simple and has controllable parameters and is suitable for industrial large-scale production.
[0007] A fourth object of the present invention is to provide a battery having higher cycle performance and safety performance.
[0008] The present invention solves the technical problem by adopting the following technical solutions.
[0009] The present invention provides a high voltage material with a single crystal particle morphology, which comprises 97.5% to 99.5% of a main material, 0.3% to 1.0% of a doping substance and 0.2% to 1.5% of a coating material according to mass fraction, wherein the chemical formula of the main material is Lix Ni 1-y-z Co y Mn z O 2 , wherein 0.95≤x≤1.15, 0.1≤y≤0.30, 0.2≤z≤0.40, the doping material is doped into the main material, and the doping material is selected from one or more of Ba, Ca, Ti, Sr, Nb, W, Mg, Zr, and Al, the coating material is coated on the surface of the main material, and the coating material is selected from Al 2 TiO 5 、ZrTiO 4 MgTiO 3 One or more of .
[0010] The present invention provides a method for preparing a high voltage material having a single crystal particle morphology, comprising the following steps:
[0011] S1. Weigh solid nickel salt, solid cobalt salt, solid manganese salt, lithium compound, the coating material and the oxide or acid salt of the doping material respectively according to the mass fraction and the stoichiometric ratio of each element in the main material;
[0012] S2, subjecting the solid nickel salt, the solid cobalt salt, the solid manganese salt, the lithium compound and the oxide or acid salt of the doping substance to high-speed ball milling to obtain a solid mixture, and calcining to obtain a main crystalline phase;
[0013] S3, mixing the main crystal phase and the coating material at a high speed, and calcining to obtain the high voltage material with a single crystal particle morphology.
[0014] The present invention provides a method for preparing a battery, comprising the following steps:
[0015] Adding an auxiliary agent to the high-voltage material with single crystal particle morphology, ball milling to obtain slurry, and then coating the slurry to obtain a membrane; finally, drying and compacting the membrane and combining it with a lithium sheet to obtain a battery.
[0016] The present invention provides a battery, which is manufactured according to the above-mentioned manufacturing method.
[0017] The high voltage material with single crystal particle morphology and its preparation method and battery of the embodiment of the present invention have the following beneficial effects:
[0018] The present invention mixes solid nickel salt, solid cobalt salt, solid manganese salt, lithium compound and oxide or acid salt of doping material by high-speed ball milling in a specific ratio to obtain Li x Ni 1-y-z Co y Mn z O2 +M solid mixture, you can get Li with doping material at one time x Ni 1-y-z Co y Mn z O 2 The layered structure phase components avoid the internal defects of the layered structure caused by the secondary recombination of the crystal phase caused by post-doping, and effectively solve the problem of Li x Ni 1-y-z Co y Mn z O 2 The problem of collapse. And the use of Al 2 TiO 5 、ZrTiO 4 MgTiO 3 The coating method of titanate compounds avoids the defects of oxygen position in the layered structure caused by valence changes during the sintering process of coating with a single substance, thereby effectively ensuring the stability of the layered structure. At the same time, the existence of the coating layer effectively solves the problem of electrolyte decomposition caused by direct contact reaction between the material and the electrolyte, thereby obtaining a material capable of charging and discharging at a high voltage of 4.4V.
[0019] In the preparation process of the present invention, solid compounds are used for mixing, and doping elements are introduced at one time, so the prepared high-voltage material has a single crystal morphology, high compaction density, high energy density, low residual alkali content, and good processing performance. The lithium-ion battery prepared by using the high-voltage material of the present invention not only has high cycle performance, but also improves the cycle performance and safety performance of the battery because the surface of the material is coated with a coating layer. In addition, the method of mixing solid mixtures can also avoid the problems of wastewater and waste discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 A single crystal grain morphology image of a high voltage material having a single crystal grain morphology according to Example 5 of the present invention;
[0022] Figure 2 The charge and discharge curve of the battery of Example 5 of the present invention at a voltage of 4.4V is shown. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0024] The high voltage material with single crystal particle morphology and its preparation method and battery according to the embodiment of the present invention are described in detail below.
[0025] The embodiment of the present invention provides a high voltage material with a single crystal particle morphology. The present invention provides a high voltage material with a single crystal particle morphology, which includes 97.5% to 99.5% of a main material, 0.3% to 1.0% of a doping material, and 0.2% to 1.5% of a coating material by mass fraction. The chemical formula of the main material is Li x Ni 1-y-z Co y Mn z O 2 , wherein 0.95≤x≤1.15, 0.1≤y≤0.30, 0.2≤z≤0.40, the dopant is doped into the main material, which can be expressed as Li x Ni 1-y-z Co y Mn z O 2 +M. M is a doping material, which is selected from one or more of Ba, Ca, Ti, Sr, Nb, W, Mg, Zr, and Al. The coating material is coated on the surface of the main material, and the coating material is selected from Al 2 TiO 5 、ZrTiO 4 MgTiO 3 Preferably, the coating material is selected from Al 2 TiO 5 、ZrTiO 4 One or both of the following.
[0026] Furthermore, in a preferred embodiment of the present invention, the particle size of the high voltage material having a single crystal particle morphology is 1 to 5 μm.
[0027] The present invention can effectively modify the high voltage material under the ratio of the main material, doping material and coating material, thereby obtaining a single crystal material suitable for charging and discharging at a high voltage of 4.4 V. The high voltage material has a single crystal particle morphology, high compaction density, high energy density, low residual alkali content, and good processing performance, thereby improving the safety performance of the material.
[0028] The present invention also provides a method for preparing a high voltage material having a single crystal particle morphology, comprising the following steps:
[0029] S1. According to the mass fraction and the stoichiometric ratio of each element in the main material, solid nickel salt, solid cobalt salt, solid manganese salt, lithium compound, the coating material and the oxide or acid salt of the doping substance are weighed respectively. Preferably, the oxide or acid salt of the doping substance can be selected from Nb 2 O 5 MgCO 3 、SrCO 3 、ZrO 2 One or more of .
[0030] S2, subjecting the solid nickel salt, the solid cobalt salt, the solid manganese salt, the lithium compound and the oxide or acid salt of the doping substance to high-speed ball milling to obtain a solid mixture, and calcining to obtain a main crystalline phase. Preferably, in the main crystalline phase, the mass percentage of the doping substance is 0.3-0.8wt%. In the process of obtaining the solid mixture of the present invention, no wastewater and waste are discharged, thereby effectively solving environmental protection problems.
[0031] Furthermore, in a preferred embodiment of the present invention, the time of the high-speed ball milling is 180 to 240 minutes.
[0032] Furthermore, in a preferred embodiment of the present invention, the calcination step is: calcining the solid mixture in air or oxygen atmosphere at 750-1000°C for 3-8h. More preferably, the calcination temperature is 800-900°C and the calcination time is 5h. Calcination at a lower temperature can avoid the volatilization of Li ions and the generation of impurity phases caused by high temperature.
[0033] S3, mixing the main crystalline phase and the coating material at high speed, and calcining to obtain the high voltage material with a single crystal particle morphology having a coating layer, wherein the mass ratio of the main crystalline phase to the coating material is 98.5-99.8:0.2-1.5.
[0034] Furthermore, in a preferred embodiment of the present invention, the high-speed mixing time is 60 to 120 minutes, and the calcination step is: the main crystal phase and the coating material are mixed at high speed and then calcined at 450 to 700°C for 3 to 8 hours in air or oxygen atmosphere. More preferably, the calcination temperature is 500 to 600°C and the calcination time is 4.5 hours. Calcination at a lower temperature can avoid the transition reaction between the coating layer and the main material, and effectively ensure that the coating layer is on the surface of the single crystal material.
[0035] The present invention mixes solid nickel salt, solid cobalt salt, solid manganese salt, lithium compound and oxide or acid salt of doping material by high-speed ball milling in a specific ratio to obtain Lix Ni 1-y-z Co y Mn z O 2 +M solid mixture, you can get Li with doping material at one time x Ni 1-y-z Co y Mn z O 2 The layered structure phase components avoid the internal defects of the layered structure caused by the secondary recombination of the crystal phase caused by post-doping, and effectively solve the problem of Li x Ni 1-y-z Co y Mn z O 2 The problem of collapse. And the use of Al 2 TiO 5 、ZrTiO 4 MgTiO 3 The coating method of titanate compounds avoids the defects of oxygen position in the layered structure caused by valence changes during the sintering process of coating with a single substance, thereby effectively ensuring the stability of the layered structure. At the same time, the existence of the coating layer effectively solves the problem of electrolyte decomposition caused by direct contact reaction between the material and the electrolyte, thereby obtaining a material capable of charging and discharging at a high voltage of 4.4V.
[0036] The present invention also provides a method for preparing a battery, comprising the following steps:
[0037] Adding an additive to the high-voltage material with single-crystal particle morphology, ball milling to obtain a slurry, and then coating the slurry to obtain a membrane with a thickness of about 100 μm; finally, drying and compacting the membrane and combining it with a lithium sheet to obtain a battery.
[0038] Furthermore, in a preferred embodiment of the present invention, the auxiliary agent includes a conductive agent, a binder and a solvent, the conductive agent is carbon black or graphite, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.
[0039] Furthermore, in a preferred embodiment of the present invention, the drying step is: the membrane is kept warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then kept warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter from the membrane, and the heating rate of the entire removal process is less than 50°C / h.
[0040] After the film is dried, it is rolled in a roller mill with a gap of 75-85μm to obtain a film with a certain density. It is then assembled in a glove box with an oxygen content of <0.01ppm and a water content of <0.01ppm, thereby effectively eliminating the negative effects of material oxidation and moisture absorption.
[0041] The present invention also provides a battery, which is prepared according to the above battery method.
[0042] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0043] Example 1
[0044] A battery provided in this embodiment is prepared according to the following method:
[0045] (1) According to the ratio of NCM1 in Table 1, the components were weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture was then calcined at 885° C. for 6.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM1).
[0046] (2) According to the ratio of No. 1 in Table 2, NCM1 and the coating material are weighed respectively, and then NCM1 and the coating material are mixed at high speed for 120 minutes, and then calcined at 535° C. for 4.5 hours in air or oxygen atmosphere to obtain a high voltage material.
[0047] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0048] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0049] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0050] Example 2
[0051] A battery provided in this embodiment is prepared according to the following method:
[0052] (1) According to the ratio of NCM2 in Table 1, the components were weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture was then calcined at 905° C. for 5.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM2).
[0053] (2) According to the ratio of No. 2 in Table 2, NCM2 and the coating material are weighed respectively, and then NCM2 and the coating material are mixed at high speed for 120 minutes, and then calcined at 650° C. for 5.0 hours in air or oxygen atmosphere to obtain a high voltage material.
[0054] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0055] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0056] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0057] Example 3
[0058] A battery provided in this embodiment is prepared according to the following method:
[0059] (1) According to the ratio of NCM2 in Table 1, the components were weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture was then calcined at 905° C. for 5.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM2).
[0060] (2) NCM2 and the coating material are weighed respectively according to the ratio of No. 3 in Table 2, and then NCM2 and the coating material are mixed at high speed for 120 minutes, and then calcined at 675° C. for 3.5 hours in air or oxygen atmosphere to obtain a high voltage material.
[0061] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0062] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0063] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0064] Example 4
[0065] A battery provided in this embodiment is prepared according to the following method:
[0066] (1) According to the ratio of NCM3 in Table 1, the components were weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture was then calcined at 835° C. for 7.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM3).
[0067] (2) According to the ratio of No. 4 in Table 2, NCM3 and the coating material are weighed respectively, and then NCM3 and the coating material are mixed at high speed for 120 minutes, and then calcined at 455° C. for 7.5 hours in air or oxygen atmosphere to obtain a high voltage material.
[0068] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0069] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0070] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0071] Example 5
[0072] A battery provided in this embodiment is prepared according to the following method:
[0073] (1) According to the ratio of NCM3 in Table 1, the components were weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture was then calcined at 835° C. for 7.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM3).
[0074] (2) According to the ratio of No. 5 in Table 2, NCM3 and the coating material are weighed respectively, and then NCM3 and the coating material are mixed at high speed for 120 minutes, and then calcined at 500°C for 6 hours in air or oxygen atmosphere to obtain a high voltage material. The single crystal morphology is shown in FIG. Figure 1 shown.
[0075] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0076] (4) The above film is rolled in a double-roller machine with a gap of 75 to 85 μm to obtain a film with a certain density, which is then cut into round pieces with a size of 15 mm.
[0077] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0078] Example 6
[0079] A battery provided in this embodiment is prepared according to the following method:
[0080] (1) According to the ratio of NCM4 in Table 1, the components are weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture is then calcined at 898° C. for 3.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM4).
[0081] (2) According to the ratio of No. 6 in Table 2, NCM4 and the coating material are weighed respectively, and then NCM4 and the coating material are mixed at high speed for 120 minutes, and then calcined at 500° C. for 5 hours in air or oxygen atmosphere to obtain a high voltage material.
[0082] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0083] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0084] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0085] Example 7
[0086] A battery provided in this embodiment is prepared according to the following method:
[0087] (1) According to the ratio of NCM4 in Table 1, the components are weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture is then calcined at 898° C. for 3.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM4).
[0088] (2) According to the ratio of No. 7 in Table 2, NCM4 and the coating material are weighed respectively, and then NCM4 and the coating material are mixed at high speed for 120 minutes, and then calcined at 520° C. for 4 hours in air or oxygen atmosphere to obtain a high voltage material.
[0089] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0090] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0091] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0092] Example 8
[0093] A battery provided in this embodiment is prepared according to the following method:
[0094] (1) According to the ratio of NCM5 in Table 1, each component is weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture is then calcined at 870° C. for 4.5 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM5).
[0095] (2) NCM5 and the coating material are weighed respectively according to the ratio of No. 8 in Table 2, and then NCM5 and the coating material are mixed at high speed for 120 minutes, and then calcined at 630° C. for 5.5 hours in air or oxygen atmosphere to obtain a high voltage material.
[0096] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0097] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0098] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0099] Example 9
[0100] A battery provided in this embodiment is prepared according to the following method:
[0101] (1) According to the ratio of NCM6 in Table 1, the components are weighed, mixed, and then high-speed ball milled for 180 min to obtain a solid mixture. The solid mixture is then calcined at 950° C. for 6.0 h in air or oxygen atmosphere to obtain the main crystalline phase (NCM6).
[0102] (2) NCM6 and the coating material are weighed respectively according to the ratio of No. 9 in Table 2, and then NCM6 and the coating material are mixed at high speed for 120 minutes, and then calcined at 450° C. for 4 hours in air or oxygen atmosphere to obtain a high voltage material.
[0103] (3) Add appropriate amounts of carbon black, polyvinylidene fluoride and N-methylpyrrolidone to the high voltage material, and use zirconium oxide balls as ball milling media to ball mill for 2 hours in a ball mill to obtain a slurry. The slurry is coated and dried to obtain a membrane with a thickness of about 100 μm. The drying steps are: keep warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then keep warm for 12 hours at 110°C and -0.1MPa vacuum to remove organic matter in the membrane. The heating rate of the entire removal process is required to be less than 50°C / h.
[0104] (4) The film is rolled in a double-roller machine at a gap of 75 to 85 μm to obtain a film of a certain density, which is then cut into discs of 15 mm in size.
[0105] (5) Assemble the membrane obtained in step (4) and the Li sheet in a glove box with an oxygen content of less than 0.01 ppm and a water content of less than 0.01 ppm to obtain a battery sample.
[0106] Table 1 Single crystal material ratio table
[0107]
[0108] Table 2 Coating ratio table
[0109]
[0110] Test Example 1
[0111] In this test example, the battery samples prepared in Examples 1 to 9 were subjected to performance tests at a voltage of 4.4 V. The test results are shown in Table 3.
[0112] Table 3 Performance test results
[0113]
[0114]
[0115] like Figure 2 The charge and discharge curve of the battery prepared in Example 5 at a voltage of 4.4 V is shown. Figure 2 It can be seen that the preparation methods of Examples 1 to 9 can obtain single crystal materials with a single crystal morphology, high compaction density, high energy density, low residual alkali content, good processing performance, and a grain size of 1 to 5 um. The material can obtain a discharge specific capacity greater than 180 mAh / g under a high voltage of 4.4 V. The material is not only simple in preparation method, but also can avoid environmental problems such as wastewater and waste discharge during the production process.
[0116] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A high voltage material having a single crystal particle morphology, characterized in that: According to the mass fraction, it includes 97.5% to 99.5% of the main material, 0.3% to 1.0% of the doping material and 0.2% to 1.5% of the coating material, and the chemical formula of the main material is Li x Ni 1-y-z Co y Mn z O2, wherein 0.95≤x≤1.15, 0.1≤y≤0.30, 0.2≤z≤0.40, the doping material is doped into the main material, and the doping material is selected from one or more of Ba, Ca, Ti, Sr, Nb, W, Mg, Zr, and Al, and the coating material is coated on the surface of the main material, and the coating material is selected from one or more of Al2TiO5, ZrTiO4, and MgTiO3.
2. The high voltage material having a single crystal particle morphology according to claim 1, characterized in that: The particle size of the high voltage material with single crystal particle morphology is 1 to 5 μm.
3. A method for preparing a high voltage material having a single crystal particle morphology, characterized in that: The following steps are involved: S1. According to the mass fractions and stoichiometric ratios of the elements in the main material as described in claims 1 to 2, respectively weigh solid nickel salt, solid cobalt salt, solid manganese salt, lithium compound, the coating material and the oxide or acid salt of the doping material; S2, subjecting the solid nickel salt, the solid cobalt salt, the solid manganese salt, the lithium compound and the oxide or acid salt of the doping substance to high-speed ball milling to obtain a solid mixture, and calcining to obtain a main crystalline phase; S3, mixing the main crystal phase and the coating material at a high speed, and calcining to obtain the high voltage material with a single crystal particle morphology.
4. The preparation method according to claim 3, characterized in that: In step S2, the high-speed ball milling time is 180 to 240 minutes.
5. The preparation method according to claim 3, characterized in that: In step S2, the calcination step is: calcining the solid mixture in air or oxygen atmosphere at 750-1000° C. for 3-8 hours.
6. The preparation method according to claim 3, characterized in that: In step S3, the high-speed mixing time is 60 to 120 minutes, and the calcination step is: the main crystal phase and the coating material are mixed at high speed and then calcined at 450 to 700° C. for 3 to 8 hours in air or oxygen atmosphere.
7. A method for preparing a battery, characterized in that: The following steps are involved: Adding an auxiliary agent to the high-voltage material with single crystal particle morphology, ball milling to obtain slurry, and then coating the slurry to obtain a membrane; finally, drying and compacting the membrane and combining it with a lithium sheet to obtain a battery.
8. The preparation method according to claim 7, characterized in that: The auxiliary agent comprises a conductive agent, a binder and a solvent. The conductive agent is carbon black or graphite, the binder is polyvinylidene fluoride, and the solvent is N-methylpyrrolidone.
9. The preparation method according to claim 7, characterized in that: The drying step is: the membrane is kept warm for 3 hours under atmospheric conditions of 50°C to 65°C, and then kept warm for 12 hours at 110°C and -0.1MPa vacuum, with a heating rate of less than 50°C / h.
10. A battery, characterized in that: Prepared according to the preparation method according to any one of claims 7 to 9.